Bovine colostrum is a health food supplement which prevents NSAID induced gut damage. Issue 5 (1st May 1999) - Playford, R J; Floyd, D N; Macdonald, C E; Calnan, D P; Adenekan, R O; Johnson, W; Goodlad, R A; Marchbank, T
Abstract : BACKGROUND: Non-steroidal anti-inflammatory drugs (NSAIDs) are effective for arthritis but cause gastrointestinal injury. Bovine colostrum is a rich source of growth factors and is marketed as a health food supplement. AIMS: To examine whether spray dried, defatted colostrum or milk preparations could reduce gastrointestinal injury caused by indomethacin. METHODS: Effects of test solutions, administered orally, were examined using an indomethacin restraint rat model of gastric damage and an indomethacin mouse model of small intestinal injury. Effects on migration of the human colonic carcinoma cell line HT-29 and rat small intestinal cell line RIE-1 were assessed using a wounded monolayer assay system (used as an in vitro model of wound repair) and effects on proliferation determined using [ 3 H]thymidine incorporation. RESULTS: Pretreatment with 0.5 or 1 ml colostral preparation reduced gastric injury by 30% and 60% respectively in rats. A milk preparation was much less efficacious. Recombinant transforming growth factor β added at a dose similar to that found in the colostrum preparation (12.5 ng/rat), reduced injury by about 60%. Addition of colostrum to drinking water (10% vol/vol) prevented villus shortening in the mouse model of small intestinal injury. Addition of milk preparation was ineffective. Colostrum increased proliferation and cell migration of RIE-1 and HT-29 cells. These effects were mainly due to constituents of the colostrum with molecular weights greater than 30 kDa. CONCLUSIONS: Bovine colostrum could provide a novel, inexpensive approach for the prevention and treatment of the injurious effects of NSAIDs on the gut and may also be of value for the treatment of other ulcerative conditions of the bowel.